Implementasi Peraturan Daerah Kabupaten Karo Nomor 2 Tahun 2018 tentang Hari Jadi Kabupaten Karo - Herawati, Riana; Sihombing, Marlon; Warjio, Warjio; Kadir, Abdul (Universitas Medan Area, 2020)
The purpose of this study was to analyze the factors that influence the implementation of the Karo District Regulation number 2 of 2018 regarding the anniversary of Karo District. The method used is descriptive qualitative research methods. The results showed the implementation of the Karo District Regulation No. 2 of 2018 on the Anniversary of the Karo District could be said to have been running optimally. This is seen from the communication aspect in the form of socialization carried out by the Regional Autonomy Section of the Karo Regency Regional Secretariat to all Local Government Agencies and Communities throughout the Karo Regency. Judging from the non-human resources, the facilities in the activities of the anniversary were quite adequate for all of the activities of the anniversary. This is evidenced by the implementation of the anniversary on March 8, 2018 in Jambo Karo District with a variety of series of activities ranging from pilgrimage to the tomb of the hero to entertainment activities. The influencing factors, namely the inhibiting factors are the lack of human resources (HR), lack of budget and lack of some of the trust of the people of Karo. Supporting factors are support from the local government, inculcation of employee awareness as the State Civil Apparatus (ASN) and accessibility factors.